The Implementation of The Quizalize Application in Improving Academic Writing Skills of EFL Students - Fuad Barakawan; Dwi Fita Heriyawati (Universitas Cokroaminoto Palopo, 2024)
The objective of this investigation is to look into how the Quizalize application helps students improve their writing skills. Taggart's study method is the Classroom Action study (PTK) using the Kemmis and Mc model. The research subjects consisted of 27 seventh-grade students. The research findings indicate that using the Quizalize application can considerably improve pupils' writing skills. Using game-based learning media like Quizalize increases students' activity, enthusiasm, and involvement in the teaching and learning process. This positively affects student achievement and learning outcomes. keywords: Writing skills, Quizalize App, Class Action Research, Game-based learning media